THE ROLE OF A HEALTHY LIFESTYLE IN WOMEN IN PREVENTING GYNECOLOGICAL DISEASES - Axmedova Sayyora Muxammadovna; Rahmonova Umida Tohir kizi, Abdumannonova Khidoyatxon Ganisher kizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
A healthy lifestyle in women is a crucial factor in preventing gynecological diseases. This article analyzes nutrition, physical activity, stress management, hygiene, and hormonal balance. Preventive measures, regular check-ups, and psychological support for reproductive-aged women to reduce gynecological risks are also discussed.